Analysis Of Caffeine In Packaged Drinks Using Thin Layer Chromatography (TLC) and Spectrophotometry Method - Munir, Muhammad Abdurrahman; Emelda, Emelda; Fatmawati, Annisa; Nurhidayanti, Nurhidayanti (Department of Chemistry - Universitas Bangka Belitung, 2024)
Caffeine is a natural alkaloid compound found in plants in the leaves, seeds and fruit. The decision of the Food and Drug Supervisory Agency regarding provisions for supervision of supplements in Chapter VIII Article 18 paragraph two states that caffeine levels must not exceed 150 mg/day. The aim of this research was to find out caffeine level in energy beverages. This research method applied the UV-Vis spectrophotometry method and the TLC method. The maximum wavelength obtained in this study was 272.55 nm and the linear results and correlation coefficient obtained were obtained. The linearity value obtained at y= 0.0381x + 0.3285 with the correlation equation R2= 0.9389. Caffeine levels obtained from “brand A” energy drink powder samples for first replicate at 49.59 mg/g, second replicate was 48.78 mg/g, third replicate was 47.15 mg/g, and “brand B” sample for first replicate was 31.5625 mg/g, second replicate at 32.375 mg/g. The caffeine levels obtained in the “brand C” sample from first replicate at 59.43 mg/g, second replicate was 60.28 mg/g, and third replicate was 60.09 mg/g. The results of the standard Rf value for caffeine standard were 0.7, the “brand A” energy drink powder sample was 0.75, the “brand B” sample was 0.75 and the “brand C” was 0.75. The conclusion from this research was that the maximum wavelength was 272.55 nm, which was slightly different from the theoretical maximum wavelength of pure caffeine, namely 273 nm. The caffeine levels obtained for samples of energy drink powder from brands A and B met the requirements because it was <50 mg/package and brand C did not meet the requirements because it was >50mg/package. The Rf value results are satisfactory because they were at range 0.2-0.8.